2021
DOI: 10.1177/15480518211068735
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Turnover Intention: The Role of Mindful Leadership, Empathetic Leadership, and Self-Regulation

Abstract: This study investigates the impact of mindful and empathetic leadership on resilience and turnover intention, with self-regulation as a mediating variable. A quantitative survey was administered to 188 nurses dealing with COVID-19’s patients in Indonesia. Data were analyzed using Process v3.5 Andrew F. Hayes in SPSS. This study revealed that mindful leadership reduces turnover intention, and empathetic leadership increases resilience, while mindful leadership does not increase resilience, and empathetic leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 108 publications
2
26
0
3
Order By: Relevance
“…Other factors, such as quality employer communication and job preparedness, were also associated with decreased turnover intention among nursing home staff [ 33 ]. Moreover, leadership support was linked to decreased turnover intention among nurses [ 41 , 65 ]. A qualitative study from Iran discovered that both a positive organisational atmosphere and organisational motivation were associated with reduced turnover intention among nurses [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other factors, such as quality employer communication and job preparedness, were also associated with decreased turnover intention among nursing home staff [ 33 ]. Moreover, leadership support was linked to decreased turnover intention among nurses [ 41 , 65 ]. A qualitative study from Iran discovered that both a positive organisational atmosphere and organisational motivation were associated with reduced turnover intention among nurses [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 lists the motivating language theory's empathetic, meaning-making, and direction-giving speech. (Sullivan, 1988;Mayfield & Mayfield, 2016;Wibowo & Paramita, 2022).…”
Section: Preparatory Conditionsmentioning
confidence: 99%
“…Comparatively, locutionary (meaning-making) speech relays meaningful utterances or promises. Wibowo and Paramita (2022) suggest that empathetic leadership must compel action. Direction-giving and meaning-making may compel employee action by strengthening the correlation between illocutionary speech and organizational citizenship behavior.…”
mentioning
confidence: 99%
“…In short, identification-based trust emphasizes an emotional connection between the leader and followers, which, in turn, leads to positive outcomes (e.g., Colquitt et al, 2012;Lewicki & Bunker, 1996;Scandura & Pellegrini, 2008;Walumbwa et al, 2020;Zhu et al, 2013). For example, Wibowo and Paramita (2021) found that empathetic leadership by the supervisor increased resilience in nurses dealing with COVID-19 patients and also decreased nurse turnover intentions. Sison (2006) articulated that virtues and character strengths constitute the underpinning on which trust and effective leadership are founded.…”
Section: Identification-based Trustmentioning
confidence: 99%